2014
DOI: 10.1002/nbm.3101
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based evaluation of the metabolic profile and response to dichloroacetate of human prostate cancer cells

Abstract: The aim of this study was to evaluate the metabolic profile of human prostate cancer cells that have different metastatic potential and to determine their response to dichloroacetate (DCA) using NMR technology. Two isogenic human prostate cancer cell lines, differing in their metastatic potential [LNCaP (poorly metastatic) and LNCaP-LN3 (highly metastatic)], were studied. Metabolite ratios from NMR spectral integrals acquired at a field strength of 9.4 T using a 5-mm broadband probe with an NMR-compatible bior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Other studies in breast and prostate cell lines showed that lactate production is reduced upon DCA treatment (41)(42)(43). We observed that lactate production was reduced following DCA treatment both in vitro, just after 24 h, as well as in vivo, with a marked decrease in lactate levels after three days of treatment.…”
Section: Discussionsupporting
confidence: 65%
“…Other studies in breast and prostate cell lines showed that lactate production is reduced upon DCA treatment (41)(42)(43). We observed that lactate production was reduced following DCA treatment both in vitro, just after 24 h, as well as in vivo, with a marked decrease in lactate levels after three days of treatment.…”
Section: Discussionsupporting
confidence: 65%
“…After exposure to 10 µM of MEK inhibitor, H295R cells presented a significantly higher lactate/alanine ratio and a higher mitochondrial membrane potential after 12 and 24 hours of treatment. The increased lactate/alanine ratio is associated with cellular redox state reflecting the intracellular NADH/NAD+equilibrium . The redox system is essential in maintaining cellular homeostasis and when a redox imbalance occurs, due to higher production of reactive oxygen species (ROS) or a decrease in endogenous protective antioxidants, cells become vulnerable to apoptosis and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge facing clinicians in the management of patients is to distinguish a lethal metastatic stage from the relatively indolent stages. Although numerous researches have shown that the metastatic progression is closely related to cellular metabolism (Kailavasan et al, ), the detailed metabolic changes and their corresponding molecular mechanism still kept unclear. The variations of metabolites are better indicators of enzyme activity.…”
Section: Introductionmentioning
confidence: 99%